Unveiling the master narratives of a sample of STEM students at an urban public college in New York City - Reynoso, Krystal; Ismail, Fadel; Ávila, Daniela; Roldós, Maria Isabel (Frontiers in Sociology, 2025)
This brief research report presents how rigid STEM narratives are perceived by undergraduate students from diverse backgrounds at an urban Minority Serving Institution (MSI) in NYC. This research focuses on student voices and reveals the unique challenges, motivations, and strengths they bring to STEM. A total of 15 peer to peer qualitative interviews were conducted between May and December of 2024. Content analyses using an inductive approach was used to cross code between the interviewers and student participants using content analyses revealed key themes such as: the importance of time management support, diverse mentorship, the role of parents and family members, among others. Findings illustrate that representation and authentic support significantly impact student success. Recommendations to address barriers and proposals of supportive solutions designed to break down STEM stereotypes to serve undergraduate students from diverse backgrounds.